Burnout assessment in nurses from a general emergency service - Daniela Filipa Rocha Nobre; Isabel Cristina Mascarenhas Rabiais; Patrícia Cruz Pontífice Sousa Valente Ribeiro; Paulo Rosário Carvalho Seabra
ABSTRACT Objective: To assess the level of Burnout among nurses in a general emergency department. Method: Quantitative, descriptive, correlational and cross-sectional study. 32 nurses from a general adult emergency department answered a questionnaire to evaluate Burnout. (Copenhagen Burnout Inventory). Result: It was verified that 59.4% of the nurses presented total Burnout. Work-related burnout was the subscale with the highest average score. It was found that the lower the age and the longer the time working in the institution, the higher the level of Burnout. Longer professional experience was related to lower levels of Burnout. There were also higher scores of Burnout among participants who thought about changing their profession, their institution or their service. Conclusion: The prevalence of Burnout is high. Professional Burnout was the most critical subscale. Age and the current work are the subscales that most influence perceived Burnout